ProGriD: The transformation package for the adoption of SIRGAS2000 in Brazil - Santos, Marcos F.; Santos, Marcelo C.; Oliveira, Leonardo C.; Costa, Sonia A.; Azevedo, João B.; Galo, Maurício [UNESP] (Springer Nature, 2012)
Brazil adopted SIRGAS2000 in 2005. This adoption called for the provision of the relationships between SIRGAS2000 and the previous reference frames used for positioning, mapping and GIS, namely, the Córrego Alegre (CA) and the South American Datum of 1969 (SAD 69). Two programs were designed for this purpose. The first one, TCGeo, provided the relationships based on three-translation Similarity Transformation parameters. TCGeo was replaced in December 2008, by ProGriD. ProGriD offers, besides the same similarity transformation as TCGeo, a set of transformations based on modelling the distortions of the networks used in the various realizations of CA and SAD 69. The distortion models are represented by a grid in which each node contains a transformation value in terms of difference in latitude and in longitude. The grid follows the same specifications of the NTv2 grid, which has been used in other countries, such as Canada, USA and Australia. This paper presents ProGriD and its main functionalities and capabilities. ©Springer-Verlag Berlin Heidelberg 2012.